A first-principles examination of conducting monolayer 1T′-MX2 (M = Mo, W; X = S, Se, Te): promising catalysts for hydrogen evolution reaction and its enhancement by strain1. Issue 33 (7th September 2015) - Putungan, Darwin Barayang; Lin, Shi-Hsin; Kuo, Jer-Lai
<x xml:space="preserve">Abstract</x> We investigated the application of 1T′-MX2 (M = Mo, W; X = S, Se, Te) 2D materials as hydrogen evolution reaction (HER) catalysts using density functional theory.